Pengaruh Profitabilitas, Likuiditas, Leverage, dan Corporate Social Responsibility (CSR) Terhadap Nilai Perusahaan - M Bayu Sugiarto; Indah Permata Dewi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of profitability, liquidity, leverage, and Corporate Social Responsibility (CSR) on firm value in infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. This research uses a quantitative approach with a causal research design. The sample was selected using purposive sampling based on specific criteria. The data used are secondary data obtained from annual reports and sustainability reports. The variables are measured using ROA, CR, DER, CSRDI, and PBV. Data analysis was conducted using multiple linear regression after classical assumption tests were satisfied, followed by t-test, F-test, and coefficient of determination analysis. The results show that profitability (ROA) and leverage (DER) have a positive and significant effect on firm value, while liquidity (CR) and CSR have no significant effect. Simultaneously, all independent variables significantly affect firm value, indicating that the model is appropriate for analysis.